Factors related with COVID-19 vaccination willingness among outpatients in China - Di Zhang; Qi Cui; Junyi Xu; Jian Cai; Xiaoping Lu; Yinguang Yang (Taylor & Francis Group, 2021)
Background COVID-19 vaccination has been accepted widely. However, there are only a few reports on patients' willingness to be vaccinated. This study investigated the willingness of Chinese outpatients to accept COVID-19 vaccination as well as influencing factors. Methods A cross-sectional survey was conducted in Jiangsu province, China in December 2020. Self-administered questionnaires, which were distributed to 625 outpatients among secondary hospitals, addressed demographic characteristics, sociological characteristics, and subjective reasons. There were 522 (83.5%) participants who gave completely valid responses. Logistic regression analysis was performed to explore the risk factors for willingness of COVID-19 vaccination. Results 71.5% of participants were willing to receive the COVID-19 vaccine. "worried about contracting COVID-19" (49.6%) and "vaccines have just been introduced and need time to consider" (38.9%) were the main reasons for being willing and unwilling to receive COVID-19 vaccine, respectively. The logistic regression analysis showed that "vaccines are an effective way to prevent diseases" (OR = 5.07, 95%CI: 3.32-7.75), "the price you are willing to pay for non-free vaccines (yuan) (101-500 vs ≤100)" (OR = 1.87, 95%CI: 1.16-3.02), "per capital monthly income(yuan) (>6000 vs ≤3000)"(OR = 2.13, 95%CI: 1.03-4.41), and "self- assessed health status (Good vs Bad)" (OR = 1.71, 95%CI: 1.01-2.90) were the main risk factors for outpatients to be willing to receive the COVID-19 vaccine. Conclusions The willingness of Chinese outpatients to receive COVID-19 vaccine was not high. The government should do more to increase publicity of knowledge about COVID-19 vaccine thus increasing willingness to vaccinate, and provide free vaccine to eliminate the cost impact.